Hanukkah - Server, Jessica (Traditions and celebrations (Pebble (Firm)), 2022)
"Hanukkah is about celebrating! Often called the Festival of Lights, the eight-day celebration honors a miracle that happened long ago. During Hanukkah, people light the menorah. They sing songs. They gather with family and friends to eat special food and give gifts. Readers will discover how a shared holiday can have multiple traditions and be celebrated in all sorts of ways"--Provided by publisher.